Β-Cyclodextrin-graft-poly(amidoamine) dendrons as the nitric oxide deliver system for the chronic rhinosinusitis therapy. (1st January 2021) - Liu, Tao; Li, Guowei; Wu, Xidong; Chen, Shaohua; Zhang, Siyi; Han, Hong; Zhang, Hongbin; Luo, Xiaoning; Cai, Xiang; Ma, Dong
Abstract: Chronic rhinosinusitis (CRS) is a rather prevalent condition with a chronic inflammatory process, which is hard to cure. Herein, a new antibacterial drug, nitric oxide (NO), was used for the attempt on CRS therapy. To achieve this, a star copolymer (β-CD-PAMAM) consisting of the β-cyclodextrin (β-CD) core and seven PAMAM-G3 arms, which was designed as a low-cytotoxicity and high NO loading carrier, were synthesized and characterizied. The obtained β-CD-PAMAM/NONOate showed the effect in inhibiting and dispersing the biofilm of S. aureus, as well as the effective antibacterial performance, implying the promising application in CRS treatment. The in vivo assay confirmed that β-CD-PAMAM/NONOate displayed excellent therapy effect on CRS and significantly improved the symptoms of the experimental rats, which was no significant different in therapy effect with the clinical Rhinocort. Incorporated with its little toxicity in vitro and in vivo, the β-CD-PAMAM/NONOate was suggested a promising application in CRS therapy.